Identitas nasional dan politik luar negeri: Studi kasus diplomasi kebudayaan - Naf'an, Ahmad Arinal Huda (Maliki Interdisciplinary Journal, 2025)
A B S T R A C T Batik is one of Indonesia's cultural heritages that has been recognized by UNESCO as an Intangible Cultural Heritage. However, Malaysia's claim over batik as part of its cultural heritage has sparked diplomatic debates and cultural nationalism in both countries. This study aims to analyze how Indonesia's national identity is preserved through cultural diplomacy in response to this cultural dispute. Using a qualitative approach and case study, this research explores the diplomatic strategies implemented by the Indonesian government, including international campaigns, intellectual property reinforcement, and community involvement in preserving batik as a symbol of national identity. The findings indicate that cultural diplomacy plays a crucial role in strengthening Indonesia's position on the global stage, not only to protect its cultural heritage but also as part of foreign policy strategy in shaping the nation's image. This study provides insights for academics and policymakers on the significance of soft power in safeguarding cultural heritage and its impact on international relations.